2015
DOI: 10.11648/j.sjph.20150305.14
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practice Women of Reproductive Age Group towards Abortion Care at Debre Markos Referral Hospital, Debre Markos Ethiopia

Abstract: Back ground: Abortion is an important cause of bleeding during pregnancy. It is one of the five leading causes of maternal death in the developing world. Moreover, in developing country, abortion is the major cause of maternal mortality, which in Ethiopia safe abortion accounts 60% considering the huge number of maternal deaths due to abortion. Objective:-The main objective of this study was to assess knowledge, attitude and practice towards to abortion care among reproductive age group women at Debre Markos R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(7 reference statements)
1
8
2
Order By: Relevance
“…The study from Harari town revealed that about 35.7% of female students have knowledge towards the legislation of abortion. Again, the finding was much lower than the study done in Debra Markos hospital which was 92% [ 1 ]. Also, lower than the study conducted in other countries.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The study from Harari town revealed that about 35.7% of female students have knowledge towards the legislation of abortion. Again, the finding was much lower than the study done in Debra Markos hospital which was 92% [ 1 ]. Also, lower than the study conducted in other countries.…”
Section: Discussioncontrasting
confidence: 63%
“…The result was consistent with the study done in the Mizan Aman town in which the attitude of women toward the legalization of abortion was 54.4% [ 22 ]. But, the result was somewhat higher than study done in Armenia and Debra Markos hospital which was 30 and 23% respectively [ 1 , 13 ]. This difference might be due to the reality of the problem in the community.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Despite the change in the law and expansion of services, young women in Ethiopia report uncertainty about the legality of abortion [ 6 8 ], and explicit knowledge that abortion is legal for minors is low [ 8 , 9 ]. Beyond gaps in knowledge, concerns about cost, privacy, and judgment from providers may create barriers in adolescents’ access to formalized services, leaving them particularly vulnerable to clandestine, and potentially unsafe, abortion [ 10 , 11 ].…”
mentioning
confidence: 99%
“…abstinence followed by 75 (22.5%), mentioned condom, whereas 54 (16%) and 26 (7.8%) avoid casual sex and remain faithful to a partner respectively to be ways that a person should follow to avoid getting these diseases while the rest 41 (10.9) didn't know about it (Tables 4 and 5) [26].…”
Section: Journal Of Hospital and Medical Management Issn 2471-9781mentioning
confidence: 99%